Fatal Huge Left Free Wall Ventricular Rupture after Acute Posterior Myocardial Infarction. (8th October 2013) - Formica, Francesco; Mariani, Silvia; Ferro, Orazio; Paolini, Giovanni
Abstract : A 77-year-old man, with a recent history of an acute inferior myocardial infarction, was referred to our hospital with echocardiographic and clinical signs of left ventricular free wall rupture (LVFWR). The intraoperative finding demonstrated a huge double LVFWR. The inferoposterior wall was dramatically destroyed without any possibility to repair.